Mulheres na batalha: performances de gênero em bares com prostituição em Santa Maria - Colvero, Carolina Appel (2010)
This study deals with the construction of gender produced by women working as prostitutes in bars in the city of Santa Maria. Based on participant observation and application of semi-structured interviews obtained data that will allow to characterize these women as well as information about more subjective aspects of their lives. I established dialogue between the reality of prostitution with some feminist theories, making use also of other universes reflections on prostitution in order to consider the peculiarities inherent to the specific universe of this research.